Age and molecular subtypes: Impact on surgical decisions. Issue 1 (1st April 2014) - Pilewskie, Melissa; King, Tari A.; Rubio, Isabel T.; Dixon, J. Michael
<x xml:space="preserve">Abstract</x> Both young patient age and breast cancer molecular subtype impact local recurrence rates and long‐term prognosis for women with breast cancer. Although rates of local recurrence are consistently higher in young women and those with high‐risk molecular subtypes, this risk does not appear to be overcome by more extensive surgery. J. Surg. Oncol. 2014 110:8–14. © 2014 Wiley Periodicals, Inc.